Comparison of capillary whole blood, venous whole blood, and plasma concentrations of mefloquine, halofantrine, and desbutyl-halofantrine measured by high-performance liquid chromatography. - Ter Kuile, F; Teja-Isavatharm, P; Edstein, MD; Keeratithakul, D; Dolan, G; Nosten, F; Phaipun, L; Webster, H; White, N (1994)
Whole blood mefloquine, halofantrine, and desbutyl-halofantrine concentrations were measured by high-performance liquid chromatography in capillary blood, venous blood, and venous plasma samples from patients along the Thai/Burmese border with falciparum malaria who were treated with either mefloquine (25 mg/kg) or halofantrine (24 mg/kg or 72 mg/kg). The limits of detection for mefloquine, halofantrine, and desbutyl-halofantrine were 50, 15, and 10 ng/ml, respectively, with 200 microliters whole blood samples. There was a good linear correlation (r > 0.9) between capillary and venous blood and between whole blood and plasma for all three compounds. Mefloquine concentrations in venous and capillary blood were very similar (mean ratio 1.02, 95% confidence intervals [CI] 0.95-1.09, n = 60), but were 1.15 times higher (95% CI 1.03-1.29) in whole blood than in plasma (n = 22). The halofantrine and desbutyl-halofantrine concentrations were 1.27 (1.12-1.45, n = 23) and 1.34 (1.16-1.55, n = 24) times higher in venous compared to capillary blood, while halofantrine but not desbutyl-halofantrine concentrations were lower in whole blood than in plasma (mean ratios: halofantrine: 0.83 [0.72, 0.94], n = 39 and desbutyl-halofantrine: 1.05 [0.96-1.15], n = 41). Measurement of mefloquine, halofantrine, or desbutyl-halofantrine in capillary blood is an accurate and practical alternative to venous blood sampling, and is particularly useful for sampling with children, and under field conditions when technical facilities are limited.